2018
DOI: 10.3390/buildings8030043
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Waste Paper Cellulosic Fibers Utilization into Cement Based Building Materials

Abstract: Abstract:Recently, the utilization of renewable natural cellulosic materials, such as wood, plants, and waste paper in the preparation of building materials has attracted significant interest. This is due to their advantageous properties, low environmental impact and low cost. The objective of this paper is to investigate the influence of recycled cellulosic fibers (in the amount 0.5 wt % of the filler and binder weight) and superplasticizer (in the amount 0.5 wt % of the cement weight) on the resulting proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The flow values reduced by ~18% using 1wt.% MCC in the absence of sisal fibres and by ~24% with 0.25% sisal fibres. The reason for the decreased flow values of fresh mortars due to the presence of sisal fibres and MCC was their hydrophilic character which led to absorption of water from the mortar pastes reducing their flow properties (Cao et al, 2015;Hospodarova et al, 2018). MCC had slightly higher effect on the flow properties due to their higher surface area and ability to absorb water more quickly.…”
Section: Flow Characteristics Of Fresh Mortar Pastementioning
confidence: 99%
“…The flow values reduced by ~18% using 1wt.% MCC in the absence of sisal fibres and by ~24% with 0.25% sisal fibres. The reason for the decreased flow values of fresh mortars due to the presence of sisal fibres and MCC was their hydrophilic character which led to absorption of water from the mortar pastes reducing their flow properties (Cao et al, 2015;Hospodarova et al, 2018). MCC had slightly higher effect on the flow properties due to their higher surface area and ability to absorb water more quickly.…”
Section: Flow Characteristics Of Fresh Mortar Pastementioning
confidence: 99%
“…These data were also in compliance with other studies with similar textile synthetic and recycled fibers, which showed that 0.5% of fibrous reinforcement is efficient for increasing mechanical properties. 39,64 On the other hand, addition above 1 wt% decreased the mechanical properties of cementitious composites reinforced with cellulose fibers as mentioned by Ghasaei et al 65…”
Section: Resultsmentioning
confidence: 88%
“…Recent studies have used cellulose fibres for the development of films addressing mechanical [ 21 , 22 ] and optical properties [ 23 , 24 ]. However, a few studies have reported excellent vapor barrier properties in packaging applications [ 25 , 26 , 27 ] and their use in the construction industry [ 28 ].…”
Section: Introductionmentioning
confidence: 99%